The perinatal and obstetric outcomes of triplet conceptions at Groote Schuur Hospital in the five-year period: 1 January 2012 to 31 December 2016 - Turner, Jane (Department of Obstetrics and Gynaecology, 2022)
Background: Triplet pregnancy rates have increased over the past few decades due to the advancing maternal age at conception and assisted reproductive technology. It is well known that the risk to both the mother and fetus are greater in multiple pregnancy when compared to singleton pregnancy. Groote Schuur Hospital (GSH), as a tertiary hospital, is the main referral unit for patients with high risk pregnancies in the Metro West region of the Western Cape and provides care to women with triplet pregnancies. There are no studies in South Africa reviewing the outcomes of triplet pregnancies; this study provided the opportunity to do so. Objectives: The outcomes of all triplet pregnancies at GSH were reviewed from 1 January 2012 to 31 December 2016. The primary objective of the study was to review the fetal and neonatal outcomes of triplet pregnancies at GSH. Fetal complications included the prevalence of fetal abnormalities, miscarriage, twin to twin transfusion syndrome, intrauterine growth restriction and discordant growth, stillbirths, preterm delivery, premature rupture of membranes and low birth weight. Neonatal complications included respiratory distress syndrome or hyaline membrane disease, intraventricular haemorrhage and necrotising enterocolitis. The secondary objective was to review maternal complications and outcomes, including anaemia, hyperemesis gravidarum, hypertensive disorders, gestational diabetes, preterm labour, antepartum and postpartum haemorrhage and operative complications. The demographic information, mode of conception and mode of delivery were also included.